Institucionalização de um familiar idoso : Tomada de decisão na perspectiva da família - Dewes, Daniela Maria Schuh (2020)
The last decades were marked by an inversion in the age pyramid, with an increase in the contingent of older people compared to younger ones. Among the elderly, the segment that grows the most is the elderly elderlier, which implies demands for long-term care. Moreover, there were also changes in the organization, composition and livelihood of families, culminating in a redefinition in the way of providing care to dependent elderly people, being the institutionalization an expanding demand. It is believed that the process of decision making by institutionalizing of an elderly relative is triggered after occurrence of a crisis, and also crossed by conflicts arising from family relationships. In view of this, this research aimed to understand how the process of decision making about the institutionalization of an elderly person by the family occurs, as well as identify and describe what feelings permeate this process. For such, a multiple case study was carried out, of descriptive character and a qualitative approach, with relatives of elderly people institutionalized in two Long Term Care Institutions for the Elderly located in municipalities that make up the Northwest Mesoregion of the State of Rio Grande do Sul. The data were collected through semi structured interviews and their results expressed in two scientific productions. The first “institutionalize an elderly relative: the decision-making process and its unfolding” responds to the objective that aims to understand how happen the decision-making process about the institutionalization of an elderly relative among family members occurs. The results of this article point to a moment of crisis that precedes the decision-making process, regardless of the type of bond cultivated between family members, the decision being taken without the participation of the elderly person, even though they have their cognitive capacity preserved. The second scientific production "institutionalization of an elderly relative: what feelings permeate this transition?" Aims to identify which feelings are experienced by families across of decision-making process by institutionalization of an elderly relative, and the implications of these feelings on family dynamics throughout the process. The results reveal the occurrence of emotional turmoil during decision-making permeated by ambiguous feelings, which vary between guilt, shame, fear, insecurity, loss and even relief. Considering the need for specific care and the increase in the search for institutionalization of elderly people, the qualification of professionals who welcome the family caregiver and who support the process of transferring the elderly to the institution, becomes essential.